Satellite evidence of archaeological site looting in Egypt: 2002–2013. (17th February 2016) - Parcak, Sarah; Gathings, David; Childs, Chase; Mumford, Greg; Cline, Eric
Abstract: Abstract : Analysis of satellite imagery covering Egypt between 2002 and 2013 indicates a significant increase in looting and other damage to archaeological sites. Looting escalated dramatically from 2009 with the onset of the global economic crisis, and intensified still further with the Arab Spring in 2011. This was mirrored by an increased volume of Egyptian artefacts sold at auction, suggesting that looting is driven by external demand as well as by internal economic pressures. Satellite analysis can be used to predict the type and period of antiquities entering the market, thereby providing valuable intelligence for international policing of the illicit antiquities trade.